Effect Of Kirigami Pattern Designs On Ultra-Stretchable Conductive Polymer Mechanical Properties For Thin Film Solar Photovoltaic Application - Che Noordin, Muhammad Redzuan (2019)
Achieving stretchable conductors with high stretchability and stable conductivity is a great challenge but urgent for multifunctional electronics applications. A kirigami patterned stretchable conductive thin film solar with a highly tunable structure material. Kirigami pattern has high potential in breaking current stretchability limitation of conductive polymers, through the manipulation of the cut-geometrical pattern on the conductive polymer base or substrate material. That kirigami structures combined with thin-film active materials may be used as a simple, low-cost, lightweight and low-profile method to track solar position, thereby maximizing solar power generation. These systems provide benefits over conventional mechanisms, where additional heavy, bulky components and structural supports are often required to synchronize tracking between panels and accommodate forces due to wind loading. Type of design kirigami pattern by using thermoplastic polyurethane (TPU) substrate and analyse the effect for identify the maximum strain ability to produce stretchable conductive circuit. Each kirigami pattern will be evaluated with the changes that take place on variation- X, variation- Y1 and variation- Y2 . Tension test will be performed on the substrate by mechanical testing method (installation on vernier caliper), the substrate is stretched and assessed the effect until it is break (Full). Effects are seen to be the maximum level of capability that can be produced by the design of the kirigami pattern by obtaining the results of each variation i.e.. Variation-X1 = 153% - 173% strain, variation-Y15= 267% - 287% strains and variation-Y21 = 243%- 263% strain. This means with an increase in the cut length X and Y2 would soften the structure with a low effective modulus and increasing the hinge length Y1 would make the structure more rigid, leading to a higher strain effective modulus. The kirigami pattern results demonstrate that the effective stress-absorption through structural transformation is able to greatly enhance the stretchability. This research can also assess the appropriate kirigami pattern for use in thin film solar panels according to requirements.